Identifikasi Virus Avian Leukosis Sub Grup J pada Peternakan Ayam Petelur Komersial di Kabupaten Tangerang Tahun 2015 - Risza Hartawan; Ni Luh Putu Indi Dharmayanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Avian leukosis virus (ALV) is one of causing agents for neoplastic syndrome in commercial chicken farms. There are six sub groups of ALV in chicken including A, B, C, D and E. However, the sub group J (ALV-J) is the most alarmed and anticipated because of its severe economic repercussion. The objective of this study was to identify the presence of ALV-J in the commercial chicken farms in Tangerang District. Two identification methods were utilized including antigen capture enzyme-linked immunosorbent assay (ac-ELISA) technique and nested reverse transcriptase polymerase chain reaction (nRT-PCR) test. As results, the ac-ELISA test detected that most of 150 serum samples from 5 commercial layer farms were positive for ALV in about 86,67%. On the other hand, none of the 60 cloacal swab and 60 albumen samples was positive for presence ALV. Subsequently, testing of 45 serum samples from 5 farms using nRT-PCR showed that in about 20% of these samples were positive of ALV-J. These evidences indicated the circulation of ALV-J with other sub groups in thecommercial layer farms in Tangerang District.